Uso de vehículos aéreos no tripulados como herramientas para el manejo de viñedos - Vico, Alexandra Melanie; Lazaro, Hilario Javier; Martinez, Laura Elizabeth; Luna, Ana Belen; Gimenez, Víctor Germán; Gomez, Aldo Hector; Osorio, Horacio Ruben; Nahuel, Cesar Gabriel; Castro, Pablo (Asociación Argentina de Geofísicos y Geodestas (AAGG), 2025)
Poster